Surveying the practice of strategic planning for school excellence - Lasisi, Abbas Ayodele; Mohd Ali, Hairuddin (Penerbit UPSI, 2010)
In this present century, it is likely that school administration will continue to grow by interfacing with new and important domains such as planning and implementing appropriate program, developing goals, policies, and materials necessary to support the administration in order to achieve school excellence. It is agreed that school excellence is being achieved due to explicit strategy and committed administration. Surveying the practice of strategic planning for school excellence is a research that attempts to understand the concepts of strategic planning. It provides a process model for school managers to integrate into school development plans. This enhances the school manager's efforts in combining goals, policies and other administrative activities into an action plan. The purpose of this study is to investigate the extent of strategic planning practices in schools. This research is quantitative in nature that employed Factor analysis in explaining five strategic planning factors for school excellence. Thus, findings from 81 respondents planning-team of sub business unit of International Islamic University Malaysia (IIUM); International Islamic School (IIS) Malaysia would be of benefit to school managers, stakeholders and as well as customers for school excellence.